Aplicação de espectroscopia no infravermelho médio e calibração multivariada para quantificação de adulterantes e teor em biodiesel de óleo de palma com óleo de soja, soja residual e diesel - Teles, Edvando Souza (2016)
In this work, it was developed and validated methodologies that were based on the use of Infrared Spectroscopy Mid (MIR) combined with multivariate calibration Square Partial Least (PLS) to quantify adulterants such as soybean oil and residual soybean oil in methyl and ethyl palm biodiesels in the concentration range from 0.25 to 30.00 (%), as well as to determine methyl and ethyl palm biodiesel content in their binary mixtures with diesel in the concentration range from 0.25 to 30.00 (%). The prediction results showed that PLS models constructed are satisfactory. Errors Mean Square Forecast (RMSEP) of adulteration and content determination showed values of 0.2260 (%), with mean error (EM) with values below 1.93 (%). The models also showed a strong correlation between actual and predicted values, staying above 0.99974. No systematic errors were observed, in accordance to ASTM E1655- 05. Thus the built PLS models, may be a promising alternative in the quality control of this fuel for possible adulterations or to content determination.